Urinary Incontinence in Postmenopausal Women: Assessment of Factors Responsible - Khurshid, Wajeeha; Zafar, Bushra; Tariq, Muqadas; Rehman, Ata Ur; Khan, Asad Zia; Ismail, Ayesha; Mujtaba, Ali; Ali, Bahar; Ahmad, Fajar; Jadoon, Areeba (Biological and Clinical Sciences Research Journal, 2025)
Postmenopausal women frequently experience urinary incontinence (UI), a condition often overlooked due to social stigma and lack of awareness. This study aimed to assess the risk factors that contribute to the development of urinary incontinence in postmenopausal women. Objective: To determine the risk factors associated with the development of urinary incontinence in postmenopausal women. Methods: This is a cross-sectional study conducted at the Uro-Gynae Unit of Ayub Teaching Hospital, Abbottabad, on 126 patients, following approval from the Ethical Committee of Ayub Teaching Hospital, using a non-probability consecutive sampling technique. Data was collected through face-to-face interviews on a self-structured questionnaire. Analysis was conducted using IBM SPSS-22. Results: Among 126 postmenopausal women having urinary incontinence, 93.65% were multi-parous, and 38.10% had a BMI over 30. LMP was 1‒5 years ago in 44.44% of participants. In contrast, 55.55% of women had a history of urinary tract infections, 37.30% had a history of previous surgeries, and 27.78% were using medications such as diuretics and sedatives. Family history of UI was found in 22.22% of participants. Conclusion: Factors responsible for UI in this study are multi-parity, BMI>30, UTI, previous surgery, medication, and family history of UI. There is a need to implement measures and interventions to reduce these factors.